2013
DOI: 10.1063/1.4793523
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Influence of graphene interlayers on the interaction between cobalt phthalocyanine and Ni(111)

Abstract: The influence of graphene interlayers on electronic interface properties of cobalt phthalocyanine on Ni(111) is studied using both photoemission and X-ray absorption spectroscopy. A charge transfer associated with a redistribution of the d-electrons at the Co-atom of the phthalocyanine occurs at the interface to Ni(111). Even a graphene buffer layer cannot prevent the charge transfer at the interface to Ni(111); however, the detailed electronic situation is different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 33 publications
3
44
2
Order By: Relevance
“…This agrees with results of XPS and NEXAFS investigations of CoPc [582] and MnPc [612] on graphene/Ni (1 1 1), for which interfacial charge transfer from the Ni surface through the graphene layer to the complexes was found. Involvement of the d z 2 orbital at the metal center was discussed [582,612]. On graphene/Ru(0 0 0 1), it was found that CoPc couples with its Co d z 2 orbital to the Ru surface, while the Pc ring was decoupled by the graphene layer.…”
Section: Graphene and Boron Nitridesupporting
confidence: 92%
See 3 more Smart Citations
“…This agrees with results of XPS and NEXAFS investigations of CoPc [582] and MnPc [612] on graphene/Ni (1 1 1), for which interfacial charge transfer from the Ni surface through the graphene layer to the complexes was found. Involvement of the d z 2 orbital at the metal center was discussed [582,612]. On graphene/Ru(0 0 0 1), it was found that CoPc couples with its Co d z 2 orbital to the Ru surface, while the Pc ring was decoupled by the graphene layer.…”
Section: Graphene and Boron Nitridesupporting
confidence: 92%
“…From an HREELS study of FePc, CoPc, NiPc, CuPc and ZnPc on graphene/Ni (1 1 1), it was concluded that NiPc, CuPc and ZnPc were completely decoupled from the metal substrate, whereas for FePc and CoPc decoupling was limited to the ligand [585]. This agrees with results of XPS and NEXAFS investigations of CoPc [582] and MnPc [612] on graphene/Ni (1 1 1), for which interfacial charge transfer from the Ni surface through the graphene layer to the complexes was found. Involvement of the d z 2 orbital at the metal center was discussed [582,612].…”
Section: Graphene and Boron Nitridesupporting
confidence: 82%
See 2 more Smart Citations
“…Additionally, evidence of charge transfer at moleculegraphene-Ni(111) interfaces [15,16] and the theoretical prediction of large charge transfer from cobaltocene (CoCp 2 ) to graphene [17] would suggest that a magnetic coupling between cobaltocene and the Ni(111) surface through the graphene layer is still achievable.…”
mentioning
confidence: 99%